(untitled) (Trinity Journal of Management, IT & Media (TJMITM), 2025)
Social media has significantly influenced political and social awareness in rural communities, serving as a tool for both empowerment and misinformation. On the positive side, social media platforms enhance civic engagement, provide access to real-time information, and bridge the gap between rural and urban populations. They enable rural citizens to participate in political discourse, advocate for local issues, and mobilize support for social causes. Additionally, social media facilitates education on governance, human rights, and global events, fostering a more informed population. However, social media also presents challenges, including the spread of misinformation, political polarization, and digital illiteracy. Many rural communities lack access to fact-checking mechanisms, making them vulnerable to propaganda, fake news, and manipulation by interest groups. Moreover, limited digital literacy can lead to the misinterpretation of political and social content, sometimes exacerbating social divisions. This paper explores both the positive and negative impacts of social media on political and social awareness in rural areas, emphasizing the need for digital literacy programs and regulatory measures to maximize benefits while mitigating risks.